Faktor-Faktor Yang Mempengaruhi Kinerja Reksa Dana Saham Di Indonesia - Minadi Wijaya; Tunggul Priyatama (Majalah Imiah Manajemen & Bisnis, 2022)
Mutual Fund performance is the main consideration for investors in determining their investment decisions. The performance of Equity Funds is influenced by many determinants of whether a mutual fund performs well or is poor. This study aims to determine the effect of Fund Size, Fund Age and Past Performance on Equity Mutual Fund Performance calculated by the Sharpe method. The sample of this research is 45 Equity Mutual Fund Products with the research period 2018-2020. The sampling technique was carried out by purposive sampling with various sampling criteria. The analysis method used is panel data regression analysis. The results of this study indicate that the Fund Size variable has no positive and insignificant effect on the performance of Equity Funds, the Fund Age variable has a positive and significant effect on the performance of Equity Funds, and the Past Performance variable has a negative and significant effect on the performance of Equity Funds. Meanwhile, the variables of Fund Size, Fund Age and Past Performance simultaneously have a positive and significant effect on the performance of Equity Funds.